The capability of apple growers in Western Australia to meet the needs of downstream market intermediaries: a case study - Mohd Nawi, Nolila (Curtin University, 2009)
In this study of the Western Australia apple industry, a pluralistic methodology was employed to provide an economic and social evaluation of the various trading relationships between growers and their preferred downstream market intermediaries. Rational economic theory suggests that growers will choose to interact with those downstream customers who offer the highest prices. However, it is apparent that growers prefer to consign fruit to a number of different markets and different customers, in order to minimise risk. In selecting those downstream market intermediaries with whom they will transact, growers recognise that in order to conduct business, they must first satisfy the needs of their downstream customers. While the need to maintain a consistent supply of good quality fruit is paramount, this can result in a significant increase in costs and additional investments in infrastructure.As there are significant economies of scale in the production and subsequent packing, grading and storage of fruit, smallholder growers may find that it is more cost effective to sell the fruit they have produced to fruit packers. Furthermore, growers prefer to transact with those market intermediaries they trust. Trust is enhanced by the willingness of the market intermediary to share risks and market information in a timely fashion and to refrain from opportunistic trading practices. Nevertheless, given that growers are more certain of their costs than their returns, they may choose to transact with some market intermediaries, even although there is minimal trust in the exchange and they are subject to the exercise of coercive market power. In particular, many of the larger growers find it necessary to transact with the supermarkets in order to dispose of the volume of fruit they have available cost effectively.